Notes on species of the genus Chlaenius Bonelli, 1810 (Coleoptera: Carabidae, Chlaeniini) from four agro-climatic zones of Rajasthan, with description of two new species - Chanu, N.yaiphabi; Swaminathan, R. (Zootaxa, 2017)
Fourteen species of the genus Chlaenius from the semi-arid and sub-humid plain zones of Rajasthan (India) have been revised in this paper, including the description of two new species: Chlaenius (Lissauchenius) udaipurensis sp. nov. and Chlaenius (Chlaeniellus) pseudotristis sp. nov. A key to these species has been given with suitable line diagrams and photographs to illustrate key taxonomic characters including labrum, mentum, maxillary and labial palpi, pronotum, elytra and aedeagus.